Pulcinella’s Mouthfuls: The pulcinellate of Carlo Sigismondo Capece and the Language of Otherness - Raizen, Karen (Quaderni d'Italianistica)

(untitled) (Iter Press, 2021)
Carlo Sigismondo Capece, a member of the classicizing Arcadian Academy in Rome, was among the most influential librettists of ‘Arcadian’ opera in the 1710s and 1720s. He also wrote dozens of pulcinellate, or ‘Pulcinella plays.’ My article centers on these Pulcinella comedies. Capece’s Pulcinella, as part of a Plautine lineage of food-obsessed parasites, consistently fumbles foreign words and recasts them in culinary terms. I argue that Capece deploys the Neapolitan zanni as a marker of linguistic difference, pointing to the misunderstandings and language barriers that, in Arcadian terms, defined the city and its vulgar populace. By exploring the role of a commedia dell’arte character in academic circles in the late seventeenth and early eighteenth centuries, I tease out the connectivity between popular and elite traditions during the Baroque period, and locate strangeness in the language between them.